High Performance Liquid Chromatography Method Validation Of α-Mangostin Assay in Mangosteen (Garcinia mangostana L.) Fruit Rind Extract Formulated in Oral Solution - Liliek Nurhidayati; Siti Sofiah; Ros Sumarny; Kevin Caesar (ALCHEMY Jurnal Penelitian Kimia, 2016)
Mangosteen fruit rind extract contain a lot of antioxidants. α-Mangostin is a component in mangosteen fruit rind that has highest antioxidant effect. The oral solution containing mangosteen fruit rind extract is required an assay method for quality assessment. Determination of a very low concentration of analyte in sample with very complex matrix, such as α-mangostin in oral solution, needs a selective and sensitive method, such as high performance liquid chromatography (HPLC). In this study, α-mangostin assay was performed by reverse phase HPLC system using octadecylsilane (C18) as stationary phase,  methanol-water (90:10) as mobile phase, the flow rate is 1.0 mL/min, and the UV detector at 316 nm. The retention time of α-mangostin was 9.622 minutes. Peak of α-mangostin was well separated with resolution of 1.725. Linearity was in the range of 1.67-5.01 ppm with correlation coefficient of 0.9986. The relative standard deviation (RSD) was 1.30 %, the recovery was in the range of 95.80-100.76